Water Intake in Growing Beef Cattle - C. M. Ahlberg; K. Allwardt; A Broocks; K Bruno; A. Taylor; C. Krehbiel; C. Richards; S. Place; U. DeSilva; D. VanOverbeke; R. Mateescu; M. M. Rolf (Kansas Agricultural Experiment Station Research Reports, 2017)
Water is an essential part of livestock and human diets and is often thought of as an inexpensive, readily available renewable natural resource. However, the amount of competition between humans, wildlife, feed production, and livestock for high-quality water is increasing, not only from the effects of drought but from the pressure of a growing global population (Nardone et al., 2010). With limited resources available for production agriculture, there is a need to identify and select for efficient animals that can produce more product with fewer inputs. Although some work has been done in dairy cattle, very little data is available on individual animal water intake in modern beef cattle (Brew et al., 2011). The majority of the water intake data available in growing beef cattle is derived from dividing the total amount of water drunk in a pen divided by the number of animals in that pen (Sexson et al., 2010; Mader and Davis, 2004). Data derived from groups are not generally useful for the purposes of genetic evaluation, which aims to quantify individual animal variation in a trait for selection. However, in order to practice selection on a large scale, parameters for collecting phenotypic data must be established. The objectives of this study were to measure daily water intake on a large number of beef steers and to estimate the number of test days necessary to collect accurate water intake phenotypes.
Keywords: water intake; beef cattle; test length